Effect of media and foliar spray of primary nutrients (NPK) on growth and yield of Anthurium (Anthurium andreanum) var. Tropical under greenhouse - SUMATHI, TATTE; CHAWLA, S L; AHLAWAT, T R; PATIL, SUDHA; GURJAR, R A (The Indian Journal of Agricultural Sciences, 2018)
The present investigation was carried out to study the effect of various growing medium and foliar spray of primary nutrients (NPK) on Anthurium (Anthurium andreanum) var. Tropical under fan and pad type greenhouse. Coconut husk + charcoal (3:1) as a growing media significantly improved all the vegetative and flowering parameters. Weekly once foliar application of 30:10:10 (NPK) @ 0.2 % recorded significantly maximum plant height, number of leaves, leaf petiole and plant spread. Whereas, early flower bud emergence, early unfurling of spathe and maximum stalk length, stalk diameter, spathe length, spathe width and flower yield were recorded in plants sprayed with 12:61:40 (NPK) @ 0.2 % once in a week.